A Tale of Two Decades: War Refugees and Asylum Policy in the European Union - Maryellen Fullerton (Washington University Global Studies Law Review, 2011)
The article explores the changes in asylum policy in the European Union (EU) for the past two decades. It highlights the case of Meki Elgafaji, an employee of a British firm providing security for travel between the Baghdad airport and the Green Zone, wherein the court issued a decision on the right of war refugees to obtain asylum in the EU. It offers information on the Common European Asylum System (CEAS), noting its significance in the debate over asylum and forced migration in the U.S.
Keywords: Right of asylum – European Union countries; Right of asylum – United States; Emigration & amp; immigration – Government policy – European Union countries; Emigration & amp; immigration – Government policy – United States; War; Refugees